High-Density Lipoprotein and 4F Peptide Reduce Systemic Inflammation by Modulating Intestinal Oxidized Lipid Metabolism: Novel Hypotheses and Review of Literature - Navab, Mohamad (2012)
Oxidized phospholipids are found in the vasculature of animal models of atherosclerosis, in human atherosclerotic lesions, and in other inflammatory diseases. Oxidized phospholipids cause vascular and nonvascular cells to initiate an inflammatory reaction. Metabolites of arachidonic acid, such as 12-hydroxyeicosatetraenoic acid, can mimic some of the inflammatory properties of oxidized phospholipids. In vitro and in vivo normal high-density lipoprotein (HDL), normal apolipoprotein A-I, and apolipoprotein A-I mimetic peptides, each likely acting in a different manner, prevent the inflammatory reaction characteristic of atherosclerosis, and this is associated with decreased levels of oxidized lipids in tissues and cells. HDL from animal models of atherosclerosis or from humans with atherosclerosis or from humans or animals with other chronic inflammatory diseases does not prevent the inflammatory reaction characteristic of atherosclerosis and may even enhance the inflammatory reaction. In mice and perhaps humans, ≈30% of the steady-state plasma HDL-cholesterol pool is derived from the small intestine. The metabolism of phospholipids by gut bacteria has been recently implicated in atherosclerosis in both mice and humans. Studies with apolipoprotein A-I mimetic peptides suggest that the small intestine is a major tissue regulating systemic inflammation in mouse models of atherosclerosis and may be important for determining the functionality of HDL.